THE IMPACT OF ARTIFICIAL INTELLIGENCE ON HEALTHCARE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The advanced development of artificial intelligence (AI) in healthcare has exhibited such promise hence it revolutionizes diagnostic precision, facilitates personalized treatments, and streamlines procedures. AI has progressed from primitive rule-based systems such as MYCIN to today's last generation of AI models such as GPT-4 and Med-Gemini. AI has been quite consistent in enhancing its capabilities and bringing continuing innovation in evidence-based medicine from medical-image predictive analytics to patient monitoring. Explainable AI (XAI) helps address the main problems of trust in AI because it allows transparent and understandable machine-learning predictions on which the physician can rely. Our paper investigates the potential of AI to change the delivery of care and define the cost, access, and outcome of care for different populations within the integration of human expertise and machine efficiency in the near future. Future research would need to combine innovation with ethical considerations and achieve full adoption, with regard to its potential and quality operation in the healthcare sector.
Keywords: Intelligence artificielle; Santé; Grands modèles de langage; Intelligence artificielle explicable; Intelligence artificielle générative